What Drives Youth to Shop for Local Fashion Online? Extending the Planned Behavior Theory and Ethnocentrism - Kartikasari, Dwi; Zuliarni, Sri; Hati, Shinta Wahyu; Anggraini, Ria; Sari, Desi Ratna; Andayani, Nur Rahmah (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Introduction: Local businesses and lawmakers in emerging economies are under tremendous pressure to compete with foreign entities and comprehend consumer behavior in the setting of increasing internationalization and the growing significance of e-commerce. Main Objectives: By adding to the theory of planned behavior and consumer ethnocentrism, this study aims to find the factors that affect people's intentions to buy local products in the context of e-commerce, fashion, youth, and Indonesia. Methods: Nonprobability snowball online sampling on social media was conducted to collect 651 valid responses. Findings/Results: We used a variance-based partial least squares structural equation model to show that attitudes, perceived behavioral control, subjective norms, and consumer ethnocentrism, directly and indirectly, affect people's intentions to buy local goods online. Conclusions: In our structural model, we stress how vital consumer ethnocentrism and subjective norms are as internal and external factors for consumers. Implications: We encourage managers of local businesses and future researchers to include these concepts in their marketing plans and research. Novelty: This research shows that consumers react differently to the opposite sign of consumer ethnocentrism when they deal with subjective norms as an outside factor because of competitive mediation. Limitations: The generalizability of our findings to different countries, situations, and product categories is limited, so we suggest future research expand beyond our scope.